(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to examine the potential for integrating karate into Physical Education programs through a systematic review of 10 studies published between 2015 and 2024. The study was conducted to understand how karate can support curriculum management, training safety, and inclusive education in schools. The methods used were a literature review with a PRISMA-based selection process, thematic analysis, and narrative synthesis to identify patterns of findings across various research contexts. The results indicate that karate contributes significantly to improving physical fitness, basic motor skills, and character development in students, including discipline, self-control, and mental resilience. Karate is also considered capable of supporting inclusive education when delivered with modifications in technique and intensity to suit student needs. However, the implementation of karate in Physical Education faces several obstacles, such as a lack of skilled instructors, limited facilities, and inadequate attention to safety aspects. Overall, these findings confirm that karate has high pedagogical value and is worthy of integration into the Physical Education curriculum. However, such integration must be accompanied by systematic curriculum development, teacher training, the provision of safe facilities, and ongoing evaluation to optimally achieve learning objectives. This study provides a conceptual and practical basis for schools and policy makers to design effective and safe karate implementation in formal education contexts.